Functional Cognitive Disorder Presents High Frequency and Distinct Clinical Profile in Patients With Low Education - Borelli, Wyllians Vendramini; de Senna, Priscylla Nunes; Brum, Wagner Scheeren; Schumacher-Schuh, Artur Francisco; Zimmer, Eduardo R.; Fagundes Chaves, Márcia Lorena; Castilhos, Raphael Machado (Frontiers in Aging Neuroscience, 2022)
INTRODUCTION: Functional Cognitive Disorder (FCD) is a non-degenerative, common cause of memory complaint in patients with high educational levels. FCD has been insufficiently described in individuals with low education. Here, we investigated the frequency of FCD among individuals with low education. METHODS: We analyzed retrospectively all new referrals from primary care to a tertiary memory clinic from 2014 to 2021. Final diagnosis, diagnostic work-up, clinical and cognitive testing data were compared between FCD and other diagnoses, grouped as Neurodegenerative Disorders (NDD). A regression model was used to assess the effect of education on the diagnosis. Data is shown in Mean [SD]. RESULTS: A total of 516 individuals (70.76 [10.3] years) with low educational attainment (4.5 [3.94] years) were divided into FCD (146, 28.3%) and NDD. Compared with NDD, FCD patients showed lower age at presentation (66.2 [9.4] vs. 72.6 [10.2], p<0.001), higher MMSE scores (22.4 [6.2] vs. 14.7 [7.8], p<0.001) and Geriatric Depression Scale scores (7.4 [5.4] vs. 5.3 [3.7], p=0.0001). DISCUSSION: Surprisingly, FCD was the most frequent diagnosis in a low educational setting. However, education was not associated with FCD. Individuals presenting FCD showed a distinct clinical profile, including younger age and higher depressive scores. Strategies to identify FCD in primary care settings may benefit both patients and healthcare systems.